Zwischen Supermarktkasse und Anwaltskanzlei. Eine klassismuskritische Perspektive auf die Darstellung von Muslim:innen in evangelischen Religionsbüchern - Kamcili-Yildiz, Naciye; Keuchen, Marion (theo web. Zeitschrift für Religionspädagogik. Selig sind die Besitzlosen?!)
Der Beitrag nimmt die Darstellung muslimischer Menschen in evangelischen Religionsbüchern der Jahrgangsstufen 7/8 in den Blick und untersucht sie aus klassismuskritischer Perspektive. Im Zentrum steht die Frage, welche religiösen und sozialen Deutungsmuster in Wort und Bild vermittelt und wie diese didaktisch gerahmt werden. Die Analyse verbindet schulbuchdidaktische und gesellschaftskritische Zugänge, indem sie Karlo Meyers Konzept des „doppelten Individuenrekurses“ mit einem klassismustheoretischen Ansatz nach Markus Gamper und Annett Kupfer verknüpft. Der Beitrag leistet auch eine intersektionale Reflexion im Blick auf eine interreligiöse Religionsdidaktik und mit der Schulbuchforschung verbunden auch einen Beitrag zu einer politischen Religionspädagogik, die mehrheitsgesellschaftliche Stereotype reflektieren lernt.
Keywords: Islam; Klassismus; Diskriminierung; Schulbuchforschung; Schulbuch; Migration

Children’s Bibles in the Reformation: Martin Luther‘s „Passional“ (1529) and Wendelin Rihel‘s „Leienbibel (1540) - Keuchen, Marion (The Oxford Handbook of the Bible and the Reformation)
Through the Reformation, the Bible and education gained central importance. The Reformation principle that the Bible as Holy Scripture should be the only basis and norm for faith (sola Scriptura) emphasized the importance of reading and writing. The Reformers wanted children and laypeople to become independent church members. Teaching material was needed for school lessons, and study Bibles with pictures were produced; Martin Luther’s Little Prayer Book (1529) served as a prototype. The Lay Bible (1540) by Wendelin Rihel was a continuation of Luther’s Little Prayer Book. This innovative period laid the foundation for later children’s Bible traditions.
Keywords: Reformation children’s Bibles; Bible illustrations; lay Bible; passional; Martin Luther; Wendelin Rihel; religious education of children

Consideration of residual stresses and damage in the fracture mechanical investigation of mechanically joined structures - Weiß, Deborah; Duffe, Tobias; Joy, Tintu David; Kullmer, Gunter (Materials Research Proceedings)
Abstract. The process of joining is used in numerous sectors of the manufacturing industry, where constructions composed of individual components or metal sheets are combined to form complex structures. A straightforward and pervasive approach for joining materials of disparate natures and coated surfaces is clinching. During the clinching process, plastic deformation, residual stresses and damage are introduced into the joint. Due to time-varying service loads cracks can initiate and propagate in the vicinity of the joint which limits the lifetime of the clinched structure. In order to prevent those damage cases, it is crucial to perform fracture mechanical evaluation of cracks in the joint region. Therefore, this publication deals with the question of how plastic deformation, residual stresses and damage need to be considered for the assessment of a crack. For this purpose, simple substitute models are employed to illustrate the principles based on the clinching application example.

“I don’t believe that you believe what I believe”: an experiment on misperceptions of social norms and whistleblowing - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina (European Economic Review)

Durch Schulseelsorge Demokratiefähigkeit bilden - Keuchen, Marion; Lindemeyer, Sabine (Rituale und Spiritualität - auch für religiös ungebundene Menschen)

Dankbarkeitskoffer. Schulseelsorge in Hochschule und Schule - Keuchen, Marion

Mut zum Widerspruch. Bibelarbeit auf dem Weg zu Markus 7,24-30 - Fermor, Gotthard; Janssen, Wibke; Keuchen, Marion; Ruddat, David

Social Information Interventions under Competing Norms: Evidence from a Whistleblowing Experiment - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina (SSRN Electronic Journal)

Social Interaction and Feedback-Giving Behavior in the Sharing Economy - An Experimental Analysis - Mir Djawadi, Behnud; Wester, Lisa (SSRN Electronic Journal)

Transfer of powder-based direct coating in the injection molding process from two dimensional components to three-dimensional components - Moritzer, Elmar; Lingnau, Kai Martin (The 40th International Conference of Polymer Processing Society)

Werkstofflicher Ansatz zum adhäsiv-basierten Fügen für hochflexible TPE-Organobleche als Verstärkungsstruktur - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Influence of the processing parameters on the mechanical strenght of injection moulded BMC components for direct screwing - Held, Christian; Moritzer, Elmar (the 40th International Conference of Polymer Processing Society)

Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Experimentelle Ermittlung von Rissablenkungswinkeln bei außerphasiger Mixed-Mode-Belastung mittels einer neuartigen Probengeometrie - Weiß, Deborah; Krome, Sven; Duffe, Tobias; Kullmer, Gunter; Ostwald, Richard

Vergleich experimenteller Methoden zur Untersuchung des Aufschmelzprozesses in Einschneckenextrudern - Knaup, Felix; Brüning, Florian (Extrusion)
Keywords: Aufschmelzen; extrusion; Messtechnik

Disentangling Negative Sentiment towards Virtual Influencers: Towards a Taxonomy of Criticism - Tölle, Laura; Rehmer, Torben; Müller, Johann; Ruppel, Fynn; Trier, Matthias

Using ChatGPT for Identifying Negative Structures in Social Media Conversations - Tölle, Laura; Nolting, Max; Trier, Matthias

Method for systematic creation of test scenarios for early customer involvement - Gräßler, Iris; Ebel, Marcel; Pottebaum, Jens (Procedia CIRP)
Verification planning for engineering complex systems lacks a systematic procedure for creating test scenarios. Test scenarios can be generated by combining test cases, or by integrating test cases into pre-specified scenarios. Based on a systematic literature analysis a method is developed to simplify verification planning by creating new test scenarios and enriching existing ones. To assist the V&V engineer in planning test scenarios, a catalogue of combination premises is created to support the method. The method is evaluated in the development of a platform for emergency management. Evaluation proves that the method makes modelling of test scenarios more efficient.
Keywords: Systems Engineering; test scenario creation; verification; customer involvement